The Effect of Service Quality, Atmosphere And Location on Customer Satisfaction - Pakpahan, Diana Putri; Muis, Indra (Green Publisher, 2025)
The title of the article is The Effect of Service Quality, Atmosphere and Location on Customer Satisfaction. This research aims to determine the effect of service quality, atmosphere, and location on customer satisfaction, using a case study of Resto Arga Ni Holong in Bekasi. This is a quantitative research study, with the sample using non-probability sampling, specifically incidental sampling. The respondents consisted of 110 consumers of Resto Arga Ni Holong. Data was collected using primary and secondary data, particularly questionnaires, and analyzed using multiple linear regression with SPSS 29 for Windows. The results show that partially, the variables of restaurant atmosphere and location proved to have a significant effect on customer satisfaction. However, the service quality variable did not show a significant partial effect. Nevertheless, the three independen variables - service quality, atmosphere, and location - simultaneously influenced customer satisfaction at Resto Arga Ni Holong.